Granulocyte colony-stimulating factor-induced aortitis with temporal arteritis and monoarthritis. Issue 2 (7th February 2023) - Iida, Keisuke; Honda, Yuki; Homma, Yoichiro
Abstract : We present the case of a patient in his 80s receiving gemcitabine-cisplatin therapy for bladder cancer who developed neutropenia and was treated with filgrastim. In 10 days, the patient developed a mild fever with left jaw claudication and right knee arthritis. Contrast-enhanced CT findings indicated aortitis. Prednisolone was started for granulocyte colony-stimulating factor (G-CSF)-induced aortitis, and symptoms and elevated serum inflammatory markers resolved rapidly, allowing early discontinuation of prednisolone. Right knee arthritis relapsed at the initial follow-up. Contrast-enhanced CT revealed aortitis had disappeared. Therefore, recurrence of G-CSF-induced arthritis was suspected; prednisolone was resumed for 29 days without relapse. Most previous reports of G-CSF-induced aortitis have described inflammation of the aorta, carotid arteries and subclavian arteries; however, G-CSF-induced aortitis may present with more peripheral symptoms, such as temporal arteritis and knee arthritis. Furthermore, G-CSF-induced aortitis reportedly responds well and rapidly to prednisolone, although early discontinuation may lead to relapse.